Numerical study of unsteady interacting compressible jet flows using finite difference method for small Reynolds numbers - Eren, H (Elsevier Science Inc, 2006)
Two dimensional time-dependent flow field for interaction of jets were investigated numerically using finite difference method. The Crank-Nicholson implicit method applied the non-dimensional equations of motion for unsteady flow of the compressible fluids. Successive Over Relaxation (SOR) method was used to solve linear algebraic equations. Four different cases were studied to solve jet flow such as free jet, parallel jets, opposite jets and cross jets for Reynolds numbers 0.5 and 25 in each case. Velocity profiles and velocity vectors were given for different cases. (c) 2005 Elsevier Inc. All rights reserved.